2013
DOI: 10.1177/1089253213486524
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Silicoproteinosis by Whole-Lung Lavage

Abstract: Acute silicoproteinosis is a rare disease that occurs following a heavy inhalational exposure to silica dusts. Clinically, it resembles pulmonary alveolar proteinosis (PAP); silica exposure is thought to be a cause of secondary PAP. We describe a patient with biopsy-confirmed acute silicoproteinosis whose course was complicated by acute hypoxemic respiratory failure requiring mechanical ventilation. Without clinical improvement despite antibiotic and steroid treatment, the patient was scheduled for whole-lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
2
15
0
4
Order By: Relevance
“…In PAP, whole lung lavage (WLL) clears the accumulated material from the airspaces, and a significant body of nonrandomized evidence strongly supports the safety and efficacy of this therapeutic approach 92. Similarities between PAP and silicoproteinosis suggest that WLL may have therapeutic potential in the nonfibrotic forms of silicosis, a contention supported by case reports and series 93,94…”
Section: Emerging Treatment Optionsmentioning
confidence: 80%
“…In PAP, whole lung lavage (WLL) clears the accumulated material from the airspaces, and a significant body of nonrandomized evidence strongly supports the safety and efficacy of this therapeutic approach 92. Similarities between PAP and silicoproteinosis suggest that WLL may have therapeutic potential in the nonfibrotic forms of silicosis, a contention supported by case reports and series 93,94…”
Section: Emerging Treatment Optionsmentioning
confidence: 80%
“…In silicosis patients WLL may remove large quantities of dust, soluble materials, and inflammatory cells from the lungs and relieve respiratory symptoms, but sustained improvement in lung function parameters has not been shown in a clinical trial 1 ) . Several studies have reported WLL performed also in acute silicoproteinosis 19 , 20 ) . Karnak et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although it decreases the presence of dust particles, macrophages and cytokines on subsequent BAL analysis, and may decrease lung function decline in the short term, it does not appear to have an impact on long‐term outcomes or mortality . Furthermore, potential treatment‐related complications including respiratory failure are of serious concern …”
Section: Treatmentmentioning
confidence: 99%